Pemidanaan terhadap Pelaku Kawin Mut’ah (Kawin Kontrak) dari Perspektif Hukum Islam - Zulfiqar Bhisma Putra Rozi (CV Rewang Rencang, 2025)
Mut’ah marriage or contract marriage is a temporary marriage that is carried out in a secret manner. It is often done for sexual and economic reasons. From the perspective of positive Indonesian law, mut’ah marriage is contrary to the essence of eternal marriage as stated in the Marriage Law and the Compilation of Islamic Law. From the perspective of Islamic law, mut’ah marriage is declared haram by the majority of scholars because it is not in accordance with the purpose of marriage which prioritizes continuity, responsibility, and protection of the rights of the wife and children. Mut’ah marriage can also give rise to several criminal problems such as adultery, embezzlement of the origin of marriage, and other criminal acts. This study was conducted to examine the urgency of the probability of criminalization of perpetrators of mut’ah marriage.